E-130 Thrombectomy for superior division versus inferior division MCA occlusions: recanalization rates, MTICI scores and first pass effect. (22nd July 2018) - Kuhn, A; de Macedo Rodrigues, K; Rex, D; Massari, F; Wakhloo, A; Puri, A
Abstract : Introduction/purpose: Mechanical thrombectomy is an effective treatment for acute MCA occlusions. The goal is to achieve the best possible recanalization result in the least amount of thrombectomy passes. However, in some cases late or only incomplete MCA territory recanalization is achieved.We hypothesize that positioning of the thrombectomy device may play a role in regards to technical success of the procedure. Materials and methods: We retrospectively reviewed our institutional stroke database and identified 50 patients with distal M1 occlusions (MCA occlusions with bifurcation involved based on CTA) from January 2013 to February 2018. We then divided the patients into 3 groups depending on the distal position of the thrombectomy device and passes performed: group 1- superior M2 division only, group 2- inferior M2 division only and group 3- mixed passes. Our evaluation included first pass TICI 2C/3 success, overall TICI 2C/3 results within the groups and median number of passes needed until completion of the procedure with acceptable recanalization result (TICI 2B-3). Procedure-related complications such as SAH were recorded. Results: A total of 50 patients (29 females) were included with a mean age of 73 years (age range 32–96 years).10 patients were included in-group 1 (superior division only). First pass TICI 2C/3 result was achieved in 3 patients (30%). Overall TICI 2C/3 recanalization independent of number of passes needed was seen in 6/10 patients (60%). The median number of passes required for an acceptable TICI result were 1.5 in this group. Only one patient who required 2 passes for a TICI 2B result was found to have an asymptomatic SAH on post-procedural CT scan. 23 patients were included in-group 2 (inferior division only). First pass TICI 2C/3 result was achieved in 8 patients (57%). Overall TICI 2C/3 recanalization independent of number of passes needed was seen in 11/23 patients (48%). The median number of passes required for an acceptable TICI result were 1 in this group. In 2 patients, additional devices (aspiration and stent) were required. The patient requiring stent placement achieved a TICI score of 2A. In this group, one asymptomatic (TICI 2B result after single pass) and one symptomatic SAH (TICI 2B result after 3 passes) were observed. 14 patients were included in-group 3 (mixed passes). A 2-pass TICI 2C/3 result was achieved in 3 patients (21%). Overall TICI 2C/3 recanalization independent op number of passes needed was seen in 7 patients (50%). The median number of passes required for an acceptable TICI result were 3 in this group. SAH-complication post-procedure was seen in 6 patients (3 symptomatic). Conclusion: Successful first pass TICI 2C/3 result was most commonly achieved with a thrombectomy pass from the inferior M2 division. The least amount of thrombectomy passes needed to achieve an acceptable TICI result was seen in group 2 (inferior division only). The most SAH-related complications and highest number of passes required to achieve at least a TICI 2B result was seen in group 3 (mixed passes). A larger cohort study will be required to validate our results. Disclosures: A. Kuhn: None. K. de Macedo Rodrigues: None. D. Rex: None. F. Massari: None. A. Wakhloo: 1; C; Philips Healthcare. 2; C; Stryker Neurovascular. 3; C; Harvard Postgraduate Course, Miami Cardiovascular Institute. 4; C; InNeuroCo. A. Puri: 1; C; Stryker Neurovascular, Covidien. 2; C; Codman Neurovascular, Covidien. 4; C; InNeuroCo.